PENGARUH LOKASI DAN HARGA TERHADAP KEPUTUSAN PEDAGANG MENYEWA KIOS DI BANTO TRADE CENTER (BTC) KOTA BUKITTINGGI - Muhammad Ridwan; Sri Mariya (JURNAL BUANA, 2021)
This purpose of reaserch is to determine and analyze the effect of location and price on traders' decisions to rent kiosks at Banto Trade Center, Bukittinnggi City. This type of research is quantitative research. The technique in determining the informants is total sampling of 55 informants. Data were analyzed using linear regression on 55 traders in Banto Trade Center (BTC), Bukittinggi City. The results of the study found that the location did not have a significant effect on the decision to hire traders at the Banto Trade Center (BTC), Bukittinggi city, as well as the price which did not have a significant effect on the decision of traders to rent a kiosk at Banto Trade Center (BTC), Bukittinggi City. The location and price together do not have a significant influence on the decisions of traderst of rent kiosks at the Banto Trade Center (BTC), Bukittinggi City.